43 Actors with learning disabilities co-delivering paediatric simulation. (22nd November 2019) - Broughton, Emma; Ostler, Harriet; Riggs, Amy
Abstract : In recent years, well published reports of healthcare inequalities for patients with learning disabilities have highlighted the need to improve training opportunities for healthcare professionals caring for this patient group. Following the successful use of actors as simulated learning disability (LD) patients in adult practice, a course was developed to enhance the skills of staff caring for patients with LD in the paediatric setting. The course set out to support staff in implementing reasonable adjustments for LD patients; build effective communication skills with LD patients and their families/carers and increase awareness of the challenges that people with learning disabilities face when accessing the hospital setting. Simulation scenarios provided candidates with the opportunity to communicate effectively with actors who portrayed adolescent LD patients; implementing reasonable adjustments in order to carry out clinical interventions. Following the scenarios, debrief was led by simulation faculty, Learning Disability specialists and cinical experts. With the support of an advocate the actors were able to contribute to the debrief process, offering valuable feedback from the unique perspective of an LD patient. Qualitative data was collected via electronic candidate evaluation. Before and after the course, candidates were asked to rate their confidence in communicating with children and young people (CYP) with LD. The pre-course weighted average was 2.9/5.0 and post course 4.15/5.0, demonstrating a marked improvement. 100% of candidates found the course useful in providing a greater understanding of how to implement reasonable adjustments for CYP with learning disabilities. The course demonstrated that the use of actors with Learning Disabilities provides a successful model for enhancing the skills of clinical staff caring for patients with LD. As it continues to run, this simulation-based course goes some way in addressing the need to improve training opportunities for staff caring for LD patients.